Effect of metal additive manufacturing residual stress on post-process machining-induced stress and distortion. (15th July 2021) - Sunny, Sumair; Mathews, Ritin; Gleason, Glenn; Malik, Arif; Halley, Jeremiah
Highlights: First study on effects of DED residual stress (RS) on thin-wall, post-machining RS. DED RS reconstruction successfully demonstrated with limited neutron diffraction data. Study reveals major difference in distortion for two high-speed machining tool paths. Importance of accounting for DED RS when machining thin-walled parts is elucidated. Graphical abstract: Abstract: This work represents the first investigation into the influence of residual stress (RS) from powder-based metal additive manufacturing (AM) on the post-process machining-induced stress and distortion for thin-walled components. Machined part distortion and surface residual stress pose major challenges in several industries, including for aerospace applications involving monolithic structures. However, the influence of initial RS in the bulk material on high-speed machining-induced stress and distortion is still not well understood. This is particularly true for more recent hybrid (additive and subtractive) manufactured components in which significant tensile and compressive RS develops from the rapid thermal cycles during the AM build. It is hypothesized in this work that, even for a simple thin-walled structure, the initial RS in the AM bulk material significantly influences the RS and distortion induced by high-speed machining. It is further hypothesized that the degree of influence of the initial RS on machining-induced RS and distortion varies significantly according to the specific tool path, even for the same net material removal. To test these hypotheses, a numerical modeling approach is presented considering a thin-walled directed energy deposition (DED) structure subjected to high-speed end-milling. A compatible RS field for the DED build is established using an iterative reconstruction algorithm based on limited neutron diffraction measurements, and the full reconstructed RS field is then imposed as an initial state in the end-milling simulation that follows. To assess the influence of the initial DED RS on the machining-induced stress and distortion, as well as to examine how this influence varies with machining strategy, two different tool paths are considered for the same net material removal, both with and without considering RS inherent to the DED build. The findings reveal significant influence of the DED RS on the high-speed machining-induced distortion and RS, and further, this influence is seen to vary greatly with the machining strategy. Normalized root-mean-square differences (NRMSD) of up to 25 % and 29 %, respectively, are observed in the machining-induced RS for the two different tool paths when DED inherent RS is considered. Likewise, maximum NRMSD of up to 44 % and 40 % are revealed in the post-machining distortion for the two respective machining strategies when DED RS is included. In addition, variations observed in the stress triaxiality computed during machining suggests that inclusion of the DED RS influences the localized response of the material near the tool-workpiece interface. The technical approach demonstrated can be extended beyond hybrid manufacturing to generate important scientific insights regarding distortion and machining-induced stress for conventionally manufactured monolithic components in the aerospace and other performance-critical industries.